Strength gains consequent to ten weeks of universal or bowflex training - Marquardt, J. R. (My University, 1992)
A strength training program was undertaken to determine if a home strength training device (Schwinn Bowflex) could result in similar improvements in strength compared to a more traditional method (Universal). Seventy-two men and women, aged 20-55 yrs, were randomly assigned to Universal (U) (n = 26; M = 14, F = 12), Bowflex (B) (n = 25; M = 13, F = 12), or Control (C) (n = 21; M = 11, F = 10). Following a 1 week orientation period, Ss were tested with OEI equipment and free weights for 1 RM strength on: chest press, chest fly, shoulder press, tricep extension, bicep curl, lat pulldown, upright rows, leg extension, leg curl, and leg press. Additionally, U and B subjects were tested for 1 RM on their respective training apparatus. Ss trained 3 days per week for 10 weeks with sets, repetitions, and intensities matched between groups. Data were analyzed using repeated measures ANOVA and Tukey's post-hoc tests. There were no significant (p > .05) differences in relative strength gains between males and females, thus data were collapsed across genders. Utilizing OEI equipment and free weight testing, strength significantly (p < .05) increased in B (14.5%) and U (19.3%) with no change (p > .05) in C. The only significant (p < .05) difference between B and U were for leg curls (5 vs. 17%) and upright rows (8 vs. 15%). For the group specific testing, overall strength significantly (p < .OS) increased for both B (23.5%) and U (25.5%). Skinfold (chest, tricep, bicep, abdominal, subscapular, and suprailiac) and girth (bicep relaxed, bicep flexed, and thigh) measurements were taken with a Harpenden caliper and tape measure, respectively. There were no significant (p > .05) differences between B, U, and C groups except for the chest skinfold with U having a significant (p < .01) decrease. There were no significant (p > .05) differences between groups for girth measurements except a small but significant (p < .05) increase in the bicep flexed measurement for B (1.98) and U (2.2%). These data indicate that significant improvements in strength can be obtained using the Schwinn Bowflex, and gains are comparable to traditional resistance training methods. Changes in body composition should not be expected following a 10-week strength training study.
Keywords: Universal weight training equipment; Weight training - Equipment and supplies; Weight training - Physiological aspects; Muscle strength